1999
DOI: 10.1093/jat/23.3.141
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Drugs Used in Cases of Alleged Sexual Assault

Abstract: In recent years, there has been an increase in the number of reports in the U.S. of the use of drugs, often in conjunction with alcohol, to commit sexual assault. A study was undertaken to assess the prevalence of drug use in sexual assault cases in which substances are suspected of being involved. Law enforcement agencies, emergency rooms, and rape crisis centers across the U.S. were offered the opportunity to submit urine samples collected from victims of alleged sexual assault, where drug use was suspected,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
140
1
11

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(164 citation statements)
references
References 17 publications
12
140
1
11
Order By: Relevance
“…Used in low concentration (30-100 mg/L) this drug produces euphoria and lack of inhibitions [5] but if the concentration exceeds 500 mg/L mg amnesia, drowsiness, visual impairment and unconsciousness are obtained instead [6] and even death in the most critical cases (over 500mg/L).…”
Section: Introductionmentioning
confidence: 99%
“…Used in low concentration (30-100 mg/L) this drug produces euphoria and lack of inhibitions [5] but if the concentration exceeds 500 mg/L mg amnesia, drowsiness, visual impairment and unconsciousness are obtained instead [6] and even death in the most critical cases (over 500mg/L).…”
Section: Introductionmentioning
confidence: 99%
“…Total Number of Items (Grams Engine) and Power Scoring of e-vendors from the Middle East Individual correlations were also carried out, the Middle East and Arabic countries contribution to the e-trade on darknet was far less than that of the European Union. It has also been known that GHB substance is used to sedate victims during sexual assault incidents and rape; a linear regression (Table 1) was implemented and it was found that a positive linear relationship (R 2 score= 0.0389) exists between the number of GHB hits on Grams engine and the incidence of sexual assaults in these locations (Elsohly & Salamone, 1999;Mehling & Johansen, 2016;Schwartz et al, 2000;Varela et al, 2004). Finally, a correlation was done in relation to the total number of hits (Grams) for nine countries (regions) known of high NPS e-prevalence; Australia, Canada, European Union, France, Germany, Netherlands, Spain, United Kingdom, and the United States.…”
Section: Resultsmentioning
confidence: 99%
“…Kenevir yaygınlığı %18,2 ile %25,6 arasında, kokain yaygınlığı ise %7,7 ile %10,8 arasında bulunmuştur [51]. Cinsel saldırı kurbanlarında GHB yaygınlığı Amerika da yapılan 4 çalışmaya göre cinsel saldırı vakalarında %3 ile %4,4 arasında belirlenmiştir [52][53][54][55]. Aynı yıllarda Birleşik Krallıkta çok daha düşük bir oran (% 0,2) bulunmuştur [56].…”
Section: Cinsel Saldırıları Kolaylaştırabilen İlaçların Kullanım Yüzdunclassified